GROWTH OF Cyclotella sp. AS A STEP FOR HEAVY METAL TOXICITY TEST - Afriana Afriana; Budijono Budijono; Andri Hendrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
Abstract Toxicity is the ability of a material to cause adverse  effects when it hits the surface or body of the test organism. One of the test materials that can be used is the microalgae type Cyclotella sp. The purpose of this study was to study the ability of Cyclotella sp. as a test material meets the requirements for heavy metal toxicity tests. The growth phase of the microalgae Cyclotella sp. Observations were carried out for 17 days to see all the growth  phases of Cyclotella sp. This result indicate that there are four living phases of Cyclotella sp. It comprises of phases lag, an exponential phase, stationary phases and phases leading to death. Cyclotella sp. qualified as a test biota for a heavy metal toxicity test using phytoplankton, according to Asean- Canada Cooperative Programme on Marine Science Phase II. This is seen from the growth of cell density that exceeds the minimum limit on the fourth day of inoculation growth curve or at the beginning of an exponential phase with density of cell 123,5 x 106 cell.mL-1.The results of the literature study showed that Cyclotella sp. can be used as biota for toxity test. Keywords: Toxicity test, Cyclotella sp., Exponential, Density, Phytoplankton.